2019
DOI: 10.1137/18m1235119
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Elastic Scattering for a Random Source

Abstract: Consider the inverse random source scattering problem for the two-dimensional time-harmonic elastic wave equation with an inhomogeneous, anisotropic mass density. The source is modeled as a microlocally isotropic generalized Gaussian random function whose covariance operator is a classical pseudo-differential operator. The goal is to recover the principle symbol of the covariance operator from the displacement measured in a domain away from the source. For such a distributional source, we show that the direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…, the random function is a distribution in f ∈ W s− d 2 −ǫ,p for any ǫ > 0 and p ∈ (1, ∞) (cf. Lemma 2.6), which is rougher than those considered in [9,15,20,21]; (2) if σ = 0 and s ∈ [ d 2 , d 2 + 1), the results obtained in this paper coincides with the ones given in [20]. The paper is organized as follows.…”
supporting
confidence: 70%
“…, the random function is a distribution in f ∈ W s− d 2 −ǫ,p for any ǫ > 0 and p ∈ (1, ∞) (cf. Lemma 2.6), which is rougher than those considered in [9,15,20,21]; (2) if σ = 0 and s ∈ [ d 2 , d 2 + 1), the results obtained in this paper coincides with the ones given in [20]. The paper is organized as follows.…”
supporting
confidence: 70%
“…To get the exact expressions of B (1) jk (s, t) and C (1) jk (s, t) while s = t for numerical computation, we need to use the following asymptotic behavior of Bessel functions (see [15, (5.16.1)-(5.16.3)] and [16]): as…”
Section: Separating the Logarithmic Part Of Smentioning
confidence: 99%
“…Motivated by [13], a new model is developed for the random source, which is assumed to be a real-valued generalized microlocally isotropic Gaussian (GMIG) random field with its covariance operator being a classical pseudo-differential operator. It is shown that the principal symbol of the covariance operator can be uniquely determined by the amplitude of the near-field scattering data averaged over the frequency band, generated by a single realization of the random source, see [14,20] for acoustic waves, [14,15] for elastic waves, and [23] for biharmonic waves. The inverse random source problem for electromagnetic waves is considered in [21], where the source is modeled by a complex-valued centered GMIG random field whose real and imaginary parts are assumed to be independent and identically distributed, leading to the relation operator being zero.…”
Section: Introductionmentioning
confidence: 99%